2012
DOI: 10.1111/j.1742-4658.2012.08588.x
|View full text |Cite|
|
Sign up to set email alerts
|

The major facilitator superfamily (MFS) revisited

Abstract: The major facilitator superfamily (MFS) is the largest known superfamily of secondary carriers found in the biosphere. It is ubiquitously distributed throughout virtually all currently recognized organismal phyla. This superfamily currently (2012) consists of 74 families, each of which is usually concerned with the transport of a certain type of substrate. Many of these families, defined phylogenetically, do not include even a single member that is functionally characterized. In this article, we probe the evol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
356
1
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 406 publications
(374 citation statements)
references
References 64 publications
7
356
1
1
Order By: Relevance
“…Insertion of the second, C domain of LacY does not appear to require the equivalent regions of the domain at the initial helix of the C domain to have enhanced stability. This is despite the fact 13 that that the C domain can be expressed and folded in the absence of the N domain 32 , and that the two domains exhibit pseudo symmetry and are thought to arise from gene duplication 33 .…”
Section: Relative Stability Of Helix I and Viimentioning
confidence: 82%
“…Insertion of the second, C domain of LacY does not appear to require the equivalent regions of the domain at the initial helix of the C domain to have enhanced stability. This is despite the fact 13 that that the C domain can be expressed and folded in the absence of the N domain 32 , and that the two domains exhibit pseudo symmetry and are thought to arise from gene duplication 33 .…”
Section: Relative Stability Of Helix I and Viimentioning
confidence: 82%
“…Multiple MFS family members were differentially regulated in both Tomato-5G and resistant strains. MFS transporters are single-polypeptide carriers that work in symport/antiport (79,80), and studies in bacteria and fungi have identified roles in the transport of toxic substances (81)(82)(83). For example, overexpression of the mfsM2 gene in a sensitive strain of Botrytis cinerea, a fungal plant pathogen, led to drug-resistance levels similar to those of a fungicide-resistant B. cinerea strain (82).…”
Section: Discussionmentioning
confidence: 99%
“…The 12 transmembrane helixes are the most frequent topology of MFS transporters and believed to be the result of an ancient gene duplication of a gene encoding a single domain with six transmembrane helixes. The maintenance of both domains in a single polypeptide chain could perhaps have been favored during evolution in order to facilitate substrate recognition and conformational changes during the transport [25]. It has been reported that halves of sucrose transporters StSUT1 from Solanum tuberosum show intermolecular interactions and reconstitute sucrose transport activity similar to the intact protein [46].…”
Section: Discussionmentioning
confidence: 99%